Magnetic field sensor based on magnetic-fluid-coated long-period fiber grating. (27th May 2015) - Zhang, Nancy Meng Ying; Dong, Xinyong; Shum, Perry Ping; Hu, Dora Juan Juan; Su, Haibin; Lew, Wen Siang; Wei, Lei
Abstract: Magnetic fluid is a promising material for sensing applications due to its remarkable magneto-optic properties. An optical fiber magnetic field sensor was developed using a long-period grating (LPG) coated with magnetic fluid. Magnetic fluid undergoes magnetization, aggregation, and phase transitions when it is under an external magnetic field. Optical properties changes that induced by the magnetic field can be sensed by the LPG of which resonant wavelength and transmission minimum are highly sensitive to the change of ambient medium. We demonstrate that the proposed sensor can maintain a high sensitivity of ∼0.154 dB/Gauss at field strength of as low as ∼7.4 Gauss.